2002
DOI: 10.1177/0091270002042012012
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Enzyme Induction and Clinical Aggravation of Porphyria: The Evaluation of Human Urinary 6β‐Hydroxycortisol/Cortisol Ratio as the Index of Hepatic CYP3A4 Activity

Abstract: The clinical aspect of porphyria has been investigated, and it is well known that porphyrinogens such as estrogens and alcohol or other inducers of P450 isoenzymes exacerbate the porphyric state. However, there can be a delay in diagnosing porphyria and a difficulty in selecting safe medicine for it even today. A 21-year-old woman developed epilepsy, disturbance of mental state, and spastic tetraparesis during the convalescent period after acute viral encephalitis. She was diagnosed with porphyria after the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, induction of CYP3A4 by luseogliflozin was observed at a concentration of 10 μmol/L in vitro. However, the 6β-hydroxycortisol/cortisol ratio, a marker for CYP3A4 induction [ 16 ], did not increase after 7 days of multiple doses of up to 25 mg of luseogliflozin in patients with T2DM in a clinical study conducted in the United States of America (Taisho Pharmaceutical Co., Ltd., data on file). Therefore, luseogliflozin is unlikely to induce CYP3A4 in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, induction of CYP3A4 by luseogliflozin was observed at a concentration of 10 μmol/L in vitro. However, the 6β-hydroxycortisol/cortisol ratio, a marker for CYP3A4 induction [ 16 ], did not increase after 7 days of multiple doses of up to 25 mg of luseogliflozin in patients with T2DM in a clinical study conducted in the United States of America (Taisho Pharmaceutical Co., Ltd., data on file). Therefore, luseogliflozin is unlikely to induce CYP3A4 in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in different reported cases of porphyrias associated with the administration of epileptic drugs, significant increases were found in the urinary excretion of porphyrins, accompanied by a high degree of liver enzyme induction, evaluated using the aminopyrine breath test (3) and the urinary excretion of 6β-hydroxycortisol (4). In non-porphyric subjects treated in monotherapy with carbamazepine, McGuire et al (6) found a significant increase in the urinary excretion of porphyrins and 6β-hydroxycortisol.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of urinary ratio of 6 β-hydroxycortisol/cortisol (6 β-OHC/C) has been suggested as a simple non-invasive biochemical marker to determine the activity of CYP3A4 in human (Wilkinson, 1996;Galteau and Shamsa, 2003). Although the ratio does not always correlate with the disposition of CYP3A substrate drugs, including the typical phenotyping probe drugs such as [ 14 C]-erythromycin and midazolam (Hunt et al 1992;Watkins et al 1992;Kinirons et al 1993Kinirons et al , 1999, but recent studies have described successful utilization of the urinary ratio 6 β-OHC/C as a measure of CYP3A induction (Saima et al 2002;Uejima et al 2002;ELDesoky et al 2005;Yeo et al 2006). Furthermore, the urinary ratio has also been studied in some disease conditions to elucidate a possible correlation of CYP3A activity with disease states such as hepatic disease, thyroid disorders and cancer (NG et al 1996;Zheng et al 2001;Szucs et al 2003;Kishino et al 2004;Hoshiro et al 2006).…”
Section: Introductionmentioning
confidence: 99%